Impact Of Transurethral Resection Of Prostate On International Prostate Symptom Score And Peak Urinary Flow Rate (Bangladesh Journal of Urology, 2020)
Objectives: To evaluate urinary symptoms and quality of life in patient with BPH before and after TURP. To determine the impact of TURP on the urinary symptoms (IPSS) and peak urinary flow rate.Methods: This study is prospective study carried out between 2010 and 2011 in the department of Urology, National Institute of Kidney Diseases & Urology. Total 102 cases were selected purposively according to selection criteria. Each patient was observed and followed up at 8 weeks (1st visit), 16 weeks (2nd visit) 24 weeks (3rd visit) after transurethral resection of prostate (TURP). IPSS score, QOL score also recorded and uroflowmetry was done to see the peak urinary flow rate (Qmax) of urine and voiding time. USG was done to see post voidal residual urine volume and DRE also done in selected cases. Data was complied and statistical analysis were done using computer based software, Statistical Package for Social Science (SPSS), using paired ‘t’ test. A P value